Social Capital and The Power of Relationship: Social Capital and The Power of Relationship - Mohd Mahzan Bin Awang (Social Studies Conference Proceedings, 2022)
Social Capital and The Power of Relationship presented by MOHD MAHZAN BIN AWANG